Rhabdomyolysis associated with newer-generation anti-seizure medications (ASMs): a real-world retrospective and pharmacovigilance study - Deng, Zhenzhen; Wang, Shengfeng; Wu, Cuifang (Frontiers in Pharmacology, 2023)
Objective: Rhabdomyolysis is a potentially fatal adverse reaction mostly triggered by certain medications. Few real-world studies have shown a clear association between newer-generation antiseizure medications (ASMs) and rhabdomyolysis. We sought to quantify the risk and evaluate the clinical features and management of rhabdomyolysis associated with newer-generation ASMs.Methods: Data were retrieved from the US FDA Adverse Event Reporting System database (FAERS) from 2018 to 2022 on newer-generation ASMs to identify rhabdomyolysis events, and disproportionality analyses were conducted by estimating the reporting odds ratios (RORs) and corresponding 95% confidence intervals (CIs). Furthermore, case reports from 2012 to 31 December 2022 on newer-generation ASM-induced rhabdomyolysis were retrieved for retrospective analysis.Results: A total of 1130 rhabdomyolysis reports from the FAERS database were considered.Levetiracetam had the greatest proportion and the highest positive signal values of rhabdomyolysis.The RORs (95% CIs) for newer-generation ASMs were, in descending order, levetiracetam 8.01